THE EFFECTIVENESS OF MATHEMATICS LEARNING THROUGH THE APPLICATION OF OPEN ENDED APPROACH - Ilhamsyah; Rahmi (Faculty of Tarbiyah and Teacher Training, 2022)
This study aims to determine the effectiveness of learning mathematics through the application of the Open Ended approach at SMA Negeri 3 Jeneponto in terms of: (1) students' mathematics learning outcomes, (2) students' mathematics learning activities and (3) student responses. This research is a type of pre-experimental research involving one class as an experimental class without a control class with the One Group Pretest Posttest Design. The sample in this study was class XII MIA 1 as many as 25 students consisting of 13 boys and 12 girls. The sampling technique uses Cluster Random Sampling. This research was conducted for 5 meetings. The instruments in this study were tests to see student learning outcomes, observation sheets to observe student activities during learning, observation sheets of learning implementation to observe the teacher's ability to manage learning in accordance with lesson plans, and questionnaires to determine students' responses to learning through the application of the Open approach. ended. The results of the study show that: (1) the average score of the students' mathematics learning achievement test after the Open Ended approach is applied is 85.8 with a standard deviation of 7.9. From these data it was found that 23 students (92%) had achieved individual mastery and this meant that classical mastery had been achieved, (2) There was an increase in student learning outcomes after applying the Open Ended approach where the average gain was normalized, namely 0.76 and generally in the high category, (3) The average percentage of student activity frequency is 88.0% and reaches the active criteria, (4) Student response questionnaires show that student responses to the Open Ended approach are positive, namely 89.5%. From the results of this study, it can be concluded that the Open Ended approach is effectively applied to students of SMA Negeri 3 Jeneponto.